Talking really does matter: Lay perspectives from older people on talking about suicide in later life - Hafford-Letchfield, Trish; Hanna, Jeffrey R.; Ellmers, Toby J.; Rasmussen, Susan; Cogan, Nicola; Gleeson, Helen; Goodman, Jolie; Martin, Sophie; Walker, Patrick; Quaife, Matthew (Frontiers in Psychology, 2022)
Background. The cumulative body of research on suicidality in later life describes its unique and complex features when compared to other population groups. Yet significant gaps exist in how research informs the further development of suitable interventions. The perspectives of older people are also limited in research findings. Aims: This exploratory study aimed to (1) identify potential barriers and enablers in discussing suicide thought and its expression in later life from the perspectives of lay older people, (2) explore where opportunities might occur in approach, place, relationships and, language with older people to discuss suicide thought and its expression Method: We conducted in-depth qualitative individual interviews with 15 people aged 70-89 years. This method helped to explore older peoples own lay perspectives on suicide thought in later life, how it is expressed, their understanding of where and how people might seek support. Results. Three themes emerged: 1) intergenerational and socio-cultural differences in suicide expression; 2) The normalization of suicide thoughts in later life, and 3) the importance and difficulties of everyday discussion and opportunities to express suicide thought. Conclusion. Suicide thought and its expression appear common and normalized in later life yet remain taboo and hidden. Participants revealed how such thoughts and behaviours are typically expressed through colloquial or ‘off-hand’ remarks and comments and the importance of authentic listening. The findings highlight the importance of more informal discussions around these topics and how care professionals, practitioners and providers might frame opportunities for dialogue with people who may want to access support. Further engagement with community informed participatory research methods in which older people provide their own perspectives and experiences is important in addressing these gaps. There is a need for co-design in developing screening, assessment and signposting outside of clinical settings that can be used in everyday caring relationships with people in later life.